Pengaruh Pembangunan Jalan Lingkar Selatan Salatiga Terhadap Perubahan Karakteristik Sosial Ekonomi Penduduk di Sekitarnya - Putri, Marsista Buana; Buchori, Imam (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
The development of a new highway gives an indirect impact on socio-economic changes for people living in proximity. In the short term, the socio-economic growth will be represented from the changes in economic activities. The Salatiga Southern Ring Road has a vital role as a connector between the Northern parts of Central Java Province and the Southern parts of it. The Salatiga Southern Ring Road is a new highway which lays at Salatiga suburbs dominated by agricultural area which less developed compared to the downtown area. The existence of the Salatiga Southern Ring Road is expected to bring some influence on the regional development. The research scope is limited on the microeconomic context which focuses on the changes of economic activities of people on utilizing/exploiting the resources after the completion of the highway construction. The result shows that the socio-economic changes in Salatiga Southern Ring Road is less significant because it happen sporadically. The highway development has only contributed on the increasing accessibilityof a certain area while the socio-economic changes is an individual decision which is affected by lots of different factors on each places.